Koperasi Berbasis Komunitas Keagamaan di Kabupaten Tasikmalaya - Zainurofieq Zainurofieq (Jurnal Iman dan Spiritualitas, 2022)
It is undeniable that the dimensions of religion and development through economic activity are in the context of implementing religious teachings that, if practiced correctly, will lead to progress and benefit the people in the future. The economic development of the people in the PP Tarekat Idrisiyyah is one of the economic models based on the religious spirit that plays an important role in supporting the lives and empowerment of the people who should be in the same breath as the development that aspires to the life of the nation and state. So, the author sees the formation of a strong, solid and economically independent jam'iyyah for the people because the anti-mainstream entrepreneurship economic movement of the Idrisiyah Order is growing towards progress. Second, the impact of all economic activities has increased the militancy of the Idrisiyyah Tarekat Jam'iyyah towards the leadership in order to embrace the transcendental aspect, namely gaining the pleasure of Allah SWT through the guerrilla movement of retail businesses, plantations, travel to the cultivation of shrimp and fish ponds in the southern part of Tasikmalaya Regency which is in line with with the spirit of development. For this reason, the author tries to explain further how the Jam'iyyah Idrisiyyah entrepreneurship movement starts from historical roots, processes and results which for some other tarekat communities, especially in Indonesia, have not been so visible on the surface as a challenge to the role of religion in development. This research was conducted using the SAA research methodology, in the form of collecting written data and gathering information in the field for both actors, informants and figures who pay attention to the development of the tarekat in Indonesia.